2017
DOI: 10.1016/j.ijrefrig.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Retrofit of lower GWP alternative R449A into an existing R404A indirect supermarket refrigeration system

Abstract:  R449A is retrofitted into a R404A real supermarket refrigeration system.  Cooling capacity is lower for R449A.  COP of both refrigerants is comparable.  R449A discharge temperature is higher but still admissible.  TEWI analysis indicates that CO 2-eq. emissions of R449A are lower than R404A Abstract R404A is going to be phased out from most of the commercial refrigeration systems due to its high GWP value of 3943. R449A (GWP of 1282) has been proposed to replace R404A with only minor system modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 12 publications
0
42
0
6
Order By: Relevance
“…R448A (GWP = 1387), R449A (GWP = 1397) and R407H (GWP = 1495) are some of these HFC or HFC/HFO mixtures which may replace R404A in some supermarkets in Europe. There are few research discussing this replacement comprehensively (Makhnatch et al, 2017). In this study, R449A is selected to represent this new generation of synthetic refrigerants.…”
Section: Direct Expansion (Dx) and Indirect Hfc/hfo Solutionsmentioning
confidence: 99%
“…R448A (GWP = 1387), R449A (GWP = 1397) and R407H (GWP = 1495) are some of these HFC or HFC/HFO mixtures which may replace R404A in some supermarkets in Europe. There are few research discussing this replacement comprehensively (Makhnatch et al, 2017). In this study, R449A is selected to represent this new generation of synthetic refrigerants.…”
Section: Direct Expansion (Dx) and Indirect Hfc/hfo Solutionsmentioning
confidence: 99%
“…In addition, most of works devoted to commercial indirect systems only focused on the performance of the system and not on the energy impact against a multiplexed solution [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…R449A and R404A were compared to each other in some ways including the compressor discharge temperature, cooling capacity and GWP (Global Warming Potential). It was observed that the refrigeration system using R449A as refrigerant has advantage on the refrigeration system using R404A as GWP and energy are taken into consideration [7].…”
mentioning
confidence: 99%